Public Spaces as a Place of Memory: The Case of Izmit Fevziye Park and Its Surrounding - Özbayraktar, Mehtap; Erol, Özden Senem (ICONARCH International Congress of Architecture and Planning, 2017)
The word “publicity” means that everything that emerges in the public is visible and audible to everyone and has the widest possible space, and points to a common world for everyone. Based on this, “public spaces” involve participatory landscapes; areas publicly perceived, evaluated, and controlled; general areas of public perception and civilisation that reflect our culture, beliefs, and public value; areas which reflect the conflict of individual behaviours, social processes, and often public values; all the natural and built environments that people freely enter; and streets, squares, open spaces, and landmarks in commercial or urban use within residential areas. As can be understood from the above definitions, the public spaces are also the areas that form the physical state of the collective memory in the most concrete way. At the end of the 19th century, the study of memory in social sciences began to reveal the space-memory relation. The changes, both in Turkey and around the world, throughout history also changed the concept and creation of public space. As the public spaces change, “collective memory” changes, too. Thus people “do not remember” or “forget” the economic, political, cultural and social events that occurred in those places in the past. The public spaces where the most rapid changes and transformation can be observed over the relationship between space and memory are “those located in the historic city centres”. With the rapid change and transformation, cities and the memories of the city dwellers disappear gradually and the old spaces are forgotten or replaced with the new ones. One of the cities where this change has taken place is the city of Izmit, which has hosted many civilisations from prehistoric times to the present and is an industrial and commercial centre with its geographical location and characteristics related to its surroundings. The main aim of the study is to compare both past changes and present conditions of Fevziye Park and its surroundings, covering an important public space in Izmit. We reveal the changes and traces of memory in the area studied by categorising them into three periods based on the zoning plans, photographs, newspapers archives we obtained: The period between 1910 and 1944, the period between 1944 and 1980, and the period from 1980 to the present. According to findings of this study, with the demolishment of some buildings and areas, the place of the historical centre accommodating the Fevziye Park and its surrounding area in the “collective memory” has changed and the events attached to the time and place of this area were forgotten together with the urban elements within the city.